Pembekalan dan Pendampingan Digital Entrepreneurship Bagi UMKM Kota Bogor - Mumuh Mulyana; Zul Azhar; Rini Syarif; Mashadi Mashadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation requires micro, small, and medium enterprises not only to use digital media as promotional tools but also to develop a digital entrepreneurial mindset in business management. This community service activity aimed to improve the understanding, skills, and readiness of MSME actors in Bogor City in implementing digital entrepreneurship through training and business mentoring. The program was conducted through four stages: needs identification, training, practical mentoring, and evaluation. The participants consisted of 30 MSME actors engaged in culinary, fashion, handicraft, service, and household product sectors. The materials covered digital entrepreneurship concepts, digital business model mapping, social media optimization, marketing content creation, marketplace utilization, simple digital financial recording, and business action plan development. The results showed an increase in participants’ understanding of digital entrepreneurship, with the average pre-test score increasing from 58.40 to 84.10 in the post-test. Most participants were also able to create digital business accounts, develop a simple content calendar, improve their business profiles, and design digital marketing strategies based on customer segmentation. This activity indicates that training combined with practical mentoring can strengthen the managerial capacity of MSMEs in facing digital-based business competition. The implication highlights the importance of continuous mentoring and collaboration among universities, local government, business communities, and digital platforms to accelerate the transformation of Bogor City MSMEs into adaptive, innovative, and competitive enterprises. Keywords: digital entrepreneurship, MSMEs, business mentoring, digital marketing, Bogor City.